Application of project citizen to VAT subjects to develop 21st century skills - Fitriany, Lisa; Adi, Panggih Nur (Harmoni Sosial: Jurnal Pendidikan IPS, 2021)
To improve skills in the 21st century, the project citizen learning model is applied as a learning innovation. With this learning model, students are expected to develop their ability to work cooperatively, innovatively, creatively, and critically. The purpose of this study is to find out the application of project citizens in the subjects of Pancasila Education and Citizenship in class XI IPS MAS Nur Ibrahimiy Rantauprapat and to know the importance of project citizens in developing the skills of 21st-century students of class XI IPS MAS Nur Ibrahimy Rantauprapat. The study was conducted with triangulation in class XI IPS MAS Nur Ibrahimy Rantauprapat. This type of research is descriptive with a qualitative approach. The results are obtained: respondents who strongly agreed with implementing the project citizen learning model in MAS Nur Ibrahimy with a score of 50.64%. Who agreed with a score of 71.42%, hesitated with a score of 29.87%, disagreed with a score of 14.28%, and strongly disagreed with a score of 5.19%. The average percentage obtained from the questionnaires spread more in respondents who voted Agree (71.42%). That indicates that the actual citizen project model is applied in class XI IPS MAS Nur Ibrahimy Rantauprapat.